The status of orchid conservation in China - Jiansheng, Jia (Lankesteriana: International Journal on Orchidology, 2015)
Orchids are a flag group in plant conservation. China has not a rich orchid flora, with only about 1200 specie in about 170 genera, but it is distin- guished by having a wider range of broad ecosystem types. On orchid vegetative morphology, a feature reflecting environmental conditions, China has equal numbers of terrestrial and epiphytic (including litho- phytic) genera. This feature is quite different from the tropical zone where epiphytic orchids are majority and from the temperate regions where terrestrial orchids predominate, and is unique in the world orchids flora.